On the use of the Choquet Integral for the Collaborative Creation of Learning Objects - Dodero, Juan Manuel; Sicilia, Miguel Ángel; Fernández, Camino (Computing and Informatics, 2012)
Computer-supported collaborative knowledge creation is the continuous process of development of knowledge assets, where produced knowledge has to be assessed by the developers, taking into account a set of criteria that may keep some interdependencies. This work poses an approach for collaborative creation of learning objects in a Web-based, educational context, based upon a coordination protocol and an aggregation mechanism. The coordination protocol allows the continuous consolidation of opinions issued about the learning objects produced by a number of authors. During certain steps of the protocol, an aggregation process is performed that takes into account the inter-dependence among criteria. The results of using the Choquet integral as an aggregation operator are compared to the usual aggregation procedure based upon weighted arithmetic means.